Principles of applied reservoir simulation - Fanchi, John R. (Gulf Professional Publishing, an imprint of Elsevier, 2018)
'Principles of Applied Reservoir Simulation' provides the fundamentals on reservoir simulation topics for both early career and seasoned engineers and researchers. Enhanced with more practicality and a focus on more modern reservoir simulations, this vital reference includes applications for not only traditional oil and gas reservoir problems, but also specialised applications in geomechanics, coal gas modelling and unconventional resources.